Pemetaan Profil Risiko Keuangan Bank KBMI 4 yang Terdaftar di Bursa Efek Indonesia Periode 2021-2025 - Dewi Juliana; Egi Drajat Abdul Jabar; Yoyo Sudaryo; Eko Djoko Prabowo (Masyarakat Ekonomi Syariah Bogor, 2026)
This study maps the financial risk profile of KBMI 4 banks listed on the Indonesia Stock Exchange over the 2021-2025 period. The sample consists of Bank Central Asia, Bank Rakyat Indonesia, Bank Mandiri, and Bank Negara Indonesia. This study applies a descriptive quantitative approach using secondary data from official annual reports, published financial statements, and financial highlights. The analyzed indicators include Gross Non-Performing Loan (NPL) as a proxy for credit risk, Loan to Deposit Ratio (LDR) as a proxy for liquidity risk, Capital Adequacy Ratio (CAR) as a proxy for capital resilience, and Return on Assets (ROA) as an indicator of earnings capacity to absorb risk. The findings show that the risk profiles across banks are heterogeneous. Bank Mandiri records the lowest average Gross NPL of 1.53%, while BRI records the highest average NPL of 3.05%. BCA shows the most conservative liquidity structure with an average LDR of 70.52% and the highest capital resilience with an average CAR of 28.02%. BNI demonstrates the strongest credit quality recovery, as its NPL declined from 3.70% in 2021 to 1.90% in 2025. The study contributes by providing a comparative descriptive risk map that complements regression-based banking studies.